2006
DOI: 10.4269/ajtmh.2006.74.568
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Malaria by Magnetic Deposition Microscopy

Abstract: Although malaria contributes to a significant public health burden, malaria diagnosis relies heavily on either non-specific clinical symptoms or blood smear microscopy methods developed in the 1930s. These approaches severely misrepresent the number of infected individuals and the reservoir of parasites in malaria-endemic communities and undermine efforts to control disease. Limitations of conventional microscopy-based diagnosis center on time required to examine slides, time required to attain expertise suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 20 publications
2
64
1
1
Order By: Relevance
“…Use of the quantitative buffy coat technique, in which a 55-l blood volume is examined by use of acridine orange-coated capillary tubes (453), increased the prevalence of gametocytes from 4.6% to 19.1% (301). Magnetic deposition microscopy (MDM) is used to concentrate erythrocytic-stage malaria parasites that contain hemozoin by exploiting their paramagnetic characteristics using strong magnetic fields (529). MDM makes it possible to screen a larger blood volume, thereby improving the detection sensitivity compared to that of routine microscopy.…”
Section: Detecting Gametocytes By Microscopymentioning
confidence: 99%
“…Use of the quantitative buffy coat technique, in which a 55-l blood volume is examined by use of acridine orange-coated capillary tubes (453), increased the prevalence of gametocytes from 4.6% to 19.1% (301). Magnetic deposition microscopy (MDM) is used to concentrate erythrocytic-stage malaria parasites that contain hemozoin by exploiting their paramagnetic characteristics using strong magnetic fields (529). MDM makes it possible to screen a larger blood volume, thereby improving the detection sensitivity compared to that of routine microscopy.…”
Section: Detecting Gametocytes By Microscopymentioning
confidence: 99%
“…One of them is a microfluidic device that is cheap, requires less diagnosis time, uses small amounts of samples, and does not need a skilled technician. (4)(5)(6)(7)(8)(9)(10) Recently, hemozoin, produced by a malaria parasite invading red blood cells, is being considered as an alternative biomarker for malaria diagnosis. Many research studies demonstrated that malaria-infected red blood cells (iRBCs) show magnetic properties distinct from those of healthy red blood cells (hRBCs), as shown in Table 1, and many groups have already utilized this difference for detecting or separating iRBCs in a label-free manner on a high gradient of a magnetic field inside the microfluidic device.…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies demonstrated that malaria-infected red blood cells (iRBCs) show magnetic properties distinct from those of healthy red blood cells (hRBCs), as shown in Table 1, and many groups have already utilized this difference for detecting or separating iRBCs in a label-free manner on a high gradient of a magnetic field inside the microfluidic device. (4)(5)(6)(7)(8) However, the current design has some limitations, such as being a batch process, having low precision, or causing severe damage to iRBCs. One important issue to be resolved is the significant reduction in the magnitude of the magnetic force with distance from the magnet poles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several microfluidic devices have been developed for malaria detection, which is one of the severest parasitic blood-borne diseases and most prevalent in the poorer countries. The separation principles are mostly based on intrinsic properties of malaria-infected RBCs (iRBCs) such as dielectric differences [71], paramagnetic affinity [72], and change in stiffness [73,74] to separate or enrich them from blood for diagnostic applications. However, as iRBCs constitute ~0.01-1% in peripheral blood of malaria patients, they are not considered as rare-cell per se and thus excluded in our discussion.…”
Section: Rare-cell Separationmentioning
confidence: 99%